2016
DOI: 10.1007/s00204-016-1739-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and hazard prediction of tattoo pigments by means of pyrolysis—gas chromatography/mass spectrometry

Abstract: The implementation of regulation for tattoo ink ingredients across Europe has generated the need for analytical methods suitable to identify prohibited compounds. Common challenges of this subject are the poor solubility and the lack of volatility for most pigments and polymers applied in tattoo inks. Here, we present pyrolysis coupled to online gas chromatography and electron impact ionization mass spectrometry (py-GC/MS) as quick and reliable tool for pigment identification using both purified pigments and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 35 publications
(53 reference statements)
0
42
0
1
Order By: Relevance
“…23 are—classified as sensitizers either by manufacturers or by the European Chemical Agency (Figure D). Among these sensitizers, known carcinogens such as aniline and 3,3'‐dichlorobenzidine were also found. Aniline presents the simplest primary aromatic amine and is cleaved off by a multitude of pigments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 are—classified as sensitizers either by manufacturers or by the European Chemical Agency (Figure D). Among these sensitizers, known carcinogens such as aniline and 3,3'‐dichlorobenzidine were also found. Aniline presents the simplest primary aromatic amine and is cleaved off by a multitude of pigments.…”
Section: Resultsmentioning
confidence: 99%
“…The pigments found in this study are known to be cleaved upon sun- Figure 2D). Among these sensitizers, known carcinogens such as aniline and 3,3'-dichlorobenzidine 14,25,[28][29][30] were also found. Aniline presents the simplest primary aromatic amine and is cleaved off by a multitude of pigments.…”
Section: Sensitizing Pigment Decomposition Products Extracted From mentioning
confidence: 99%
“…Method validation and using the MALDI method for market surveys demonstrated that the method described is fit for purpose. Therefore, LDI/MALDI-TOF MS is a further powerful tool particularly in combination with py-GC/MS 10 , HPLC or ultraviolet–visible spectroscopy 18 for enforcing legal restrictions on pigments in tattoo inks and PMUs. It should be kept in mind, however, that the presented method gives no information on the levels of the detected organic pigments.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy has also been used for matching the profile of tattoo inks with dermatome shave biopsies from patients with allergic reactions 9 . Another recent paper describes the successful use of pyrolysis gas chromatography (py-GC/MS) 10 . While FT-IR and Raman Spectroscopy are very suitable for the identification of single pigments, their successful use for pigment mixtures, often present in tattoo inks, has yet to be proved.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis-gas chromatography mass spectrometry ( py-GC/MS) is a further approach helpful in the analysis of tattoo inks. 9,10 Yet, a major drawback of this is the requirement of characteristic cleavage patterns for pigment identification.…”
Section: Introductionmentioning
confidence: 99%